Analysing the discourse of knowledge transfer practices: A study of proximity in psychology-related podcasts - Ansó-Millán, Alba (Complutense Journal of English Studies, 2025)
This paper offers a study of proximity (Hyland 2010) in knowledge transfer podcasting discourse aimed at broad digital audiences. To do so, ten podcast openings were retrieved from The Psychology Podcast (Kaufman 2014-present), a popularising English-medium channel with an interview-like style. Samples of the podcaster’s and the experts’ discourse were compiled and analysed by adapting Hyland’s (2005) stance and engagement categories to podcast discourse. Results from the manual close-readings of the transcripts showed that Self mentions (SM), Attitude markers (AM), Listener mentions (LM) and Immediate addressee (IA) are particularly frequent in these podcast openings. Moreover, closer examination of the use of these rhetorical devices by the experts and by the podcaster revealed that they perform different roles. Whilst the former functions as a scientist-storyteller, narrating their personal how did I get here story, the latter acts as the main catalyst for drawing the listeners in. Building on available research into popularisations (Caliendo 2014; Scotto di Carlo 2014; Spinelli and Dann 2019; Engberg 2023b; Liu and Jiang 2024), this study will argue that podcasting discourse couples transfer of knowledge with affinity appeals to broad audiences, allowing for the creation of a space based on communication as well as personal connection.